1979
DOI: 10.1128/iai.25.1.328-336.1979
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of lipopolysaccharide on macrophages: differential phagocytic responses of C3H/HeN and C3H/HeJ macrophages in vitro

Abstract: The phenomenon of lipopolysaccharide (LPS)-induced in vitro macrophage cytotoxicity has been reported by a number of investigators but has often been difficult to reproduce and to quantitate. In this report, we have examined the effect of LPS on the ability of macrophages to ingest 51Cr-labeled, opsonized sheep erythrocytes as a method for examining the direct toxic effects of LPS on macrophages in vitro. By using this assay, we can clearly discriminate between LPS responder C3H/HeN macrophages and LPS nonresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…Antibody-mediated uptake of S-LPS. High concentrations of nonopsonized LPS are toxic to LPS-responsive macrophages (24). This observation was confirmed in this study (data not shown) and limited our ability to study the metabolism of larger amounts of cell-associated R-LPS.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Antibody-mediated uptake of S-LPS. High concentrations of nonopsonized LPS are toxic to LPS-responsive macrophages (24). This observation was confirmed in this study (data not shown) and limited our ability to study the metabolism of larger amounts of cell-associated R-LPS.…”
Section: Resultssupporting
confidence: 66%
“…(C3H/HeN mice), or from Jackson Laboratories, Bar Harbor, Maine (C3H/HeJ mice), and were stored in the animal facility of the University of Texas Health Science Center, Dallas. The mice were injected intraperitoneally with 2.0 ml of sterile Brewer thioglycolate broth (Difco Laboratories, Detroit, Mich.), and peritoneal cells were harvested 5 days later (24). In each experiment, C3H/HeN and C3H/HeJ mice of comparable ages (within 1 week) were used; all experiments were performed when the mice were 5 to 12 weeks old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Vogel et al (16), LPS induces a profound inhibition of Fc-mediated phagocytosis in LPS-responsive M4 of C3H/HeN mice. Furthermore, low concentrations of LPS stimulate phagocytosis in M4X of nonresponder C3H/HeJ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published studies used extreme pharmacologic concentrations of LPS, ranging between 50 and 1000 mg/mL, which exceed the physiologically achievable concentrations by 10 4to 10 7 -fold, to assess various biological responses. 23e27 At these extreme concentrations, LPS causes rapid cell death in various cell types studied, including intestinal and immune cells, 24,25,27,28 and does not provide accurate depiction of biological activity of LPS as of the immune response in the cells and the activation of many downstream transcription factors. In contrast, we previously showed, for the first time, that LPS at physiologically achievable concentrations (0 to 1000 pg/mL) and clinically achievable concentrations (0 to 10 ng/mL) does not cause acute cell death.…”
mentioning
confidence: 99%